PEMBUATAN GULA DAN ALKOHOL DARI BEBERAPA JENIS KAYU - Gusmailina Gusmailina; Hartoyo Hartoyo (Jurnal Penelitian Hasil Hutan, 1988)
This  article  describes   the  experiment  of  sugar and  alcohol  contents from 3  wood  species,  i.e. jelutung (Dyera costulata, Hook. F), keruing (Dipterocarpus  appendiculatus, Sheff) and  durian  (Durio excelsus, Bakb) by using hydrolysis and  fermentation process. Treatment condition for  hydrolysis  were at 3 levels of sulfuric acid concentration which were 1%, 2%, and 3%  respectively. The fermentation methods agent for producing alcohol  from  sugar of wood  hydrolysis  was the yeast  of  bread containing  Saccharomyces cereviceae.The  result  of this experiment indicated  that  the yield  of sugar ranges from  9.71 % -   11.89% with average of 1,06%. This average yield  of  sugar falls in  the  range of  the  sugar yield  obtained from other researches which have  range from 11-18%.                                                                                                                                                                                                    The  average alcohol  yield  obtained  from  sugar fermentation  was 2.62%. This yield  was lower compared  with other experiment   producing   alcohol  from  wood  abroad, i.e. 8 -   15%. The  result  showed  that  the yield  of sugar is not affected by  the  wood  species  and  low  concentration  of  sulfuric acid  treatment.